Capillary Electrophoresis-Mass Spectrometry Therapeutic Protein Characterization - Xia, James Q.; Zhang, Lichao (Springer International Publishing : Imprint: Springer, 2016)
This book covers the latest developments in capillary electrophoresis-mass spectrometry for the analysis of therapeutic proteins. The application of capillary electrophoresis-mass spectrometry (CE-MS) coupling technology in the analysis of recombinant therapeutic proteins is detailed thoroughly. Specific topics include recent developments in coupling capillary electrophoresis with mass spectrometry for the quality control of monoclonal antibody therapeutics, top-down analysis of monoclonal antibody using the CE-MS platform, and detection of host cell protein impurities. Comprehensive characterization of antibody-drug conjugates (ADCs) by coupling capillary electrophoresis with mass spectrometry is also covered. This is an ideal book for scientists in the life science and biopharmaceutical industry who are working on characterizing the PTMs of monoclonal antibodies, as well as graduate students and researchers in the separation science and biological mass spectrometry fields.